Exploring green solvent systems and enhanced solubility of xanthone in triglyceride‑based tricaprin‑tricaprylin mixtures with thermodynamic insights - Liu, Hua; Stanslas, Johnson; Ren, Jiaoyan; Suleiman, Norhidayah; Chong, Gun-Hean (BioMed Central Ltd, 2024)
This study explores the use of green solvent systems by investigating the solubility and thermodynamic properties of xanthone (1) in triglyceride-based tricaprin (2) and tricaprylin (3) mixtures, aiming to replace traditional organic solvents. The solubility profile exhibited a concave trend, and the highest solubility was observed at a solute-free fraction (x2) of 0.36. The solubility exponentially increased with increasing temperature in the range from 30 °C to 75 °C. The solubility data were effectively correlated using the local composition-regular solution theory (LC-RST) model and achieved an ARDln value of 4.8 × 10–3. The model indicated strong interactions between tricaprin and tricaprylin, followed by interactions between tricaprylin and xanthone and between tricaprin and xanthone. The dissolution process of xanthone was primarily enthalpy driven. Based on the structural analysis, xanthone maintained its molecular structure after dissolution in tricaprin and tricaprylin; however, changes in crystallinity levels were observed. These findings provide insights into the use of triglycerides as solvents to improve the solubility and bioaccessibility of hydrophobic compounds such as xanthone.